3D spatiotemporal risk assessment analysis of the tunnelling-induced settlement in an urban area using analytical hierarchy process and BIM. Issue 2 (3rd April 2022) - Providakis, Stylianos; Rogers, Chris D. F.; Chapman, David N.
ABSTRACT: Issues associated with tunnel construction and adjacent building damage risk are becoming increasingly important as cities expand and make more use of their underground space. A typical geotechnical engineering problem is how to determine the ground settlement susceptibility of buildings due to tunnelling excavations. A risk assessment, considering the analysis of several factors, is required for sustainable and resilient planning of urban areas and underground space. The Analytical Hierarchy Process (AHP) has been widely adopted for similar objectives, while AutoRegressive eXogenous modelling (ARX) as the dynamic component has the potential to produce the necessary analysis to underpin the assessment. Additionally, the database and visualisation capabilities of the Building Information Modelling (BIM) framework could provide a promising environment for accommodating such a risk assessment. The proposed methodology reported herein has employed a spatiotemporal analysis using AHP and ARX to produce analytical outcomes that involved several settlement-inducing criteria with respect to their severity and time-dependent groundwater table level changes, respectively. The integration of these analyses within the BIM framework has produced a tool that can define in detail the settlement vulnerability and building-damage assessments within a 3D geology-tunnel-buildings model.